1996
DOI: 10.1289/ehp.96104s4823
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immunity in harbour seals (Phoca vitulina) exposed to bioaccumulated environmental contaminants: review of a long-term feeding study.

Abstract: Mass mortalities among seals and dolphins inhabiting contaminated marine regions have led to speculation about a possible involvement of immunosuppression associated with environmental pollution. To evaluate whether contaminants at ambient environmental levels can affect immune function of seals, we carried out an immunotoxicological study under semifield conditions. Two groups of 1 1 harbour seals (Phoca vitulina) originating from a relatively uncontaminated area were fed herring from either the highly pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(96 citation statements)
references
References 31 publications
4
91
1
Order By: Relevance
“…These actual and predicted TEQ concentrations were compared to ∑TEQ levels observed in experiments with harbour seals [56]. Levels of 196−220 pg/g lipid weight and 58–66 pg/g lipid weight were seen for experimental and control groups of juvenile harbour seals which had been fed contaminated and uncontaminated fish respectively over a 126 week period [1], [56][62]. Impaired immune responses were found in the experimental group, and therefore ∑TEQ levels of around 200 pg/g lipid weight were considered to be immunotoxic, although Kannan et al (2000) suggest a threshold of ∼520 pg/g lipid weight for marine mammals.…”
Section: Discussionmentioning
confidence: 99%
“…These actual and predicted TEQ concentrations were compared to ∑TEQ levels observed in experiments with harbour seals [56]. Levels of 196−220 pg/g lipid weight and 58–66 pg/g lipid weight were seen for experimental and control groups of juvenile harbour seals which had been fed contaminated and uncontaminated fish respectively over a 126 week period [1], [56][62]. Impaired immune responses were found in the experimental group, and therefore ∑TEQ levels of around 200 pg/g lipid weight were considered to be immunotoxic, although Kannan et al (2000) suggest a threshold of ∼520 pg/g lipid weight for marine mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In a two-year feeding experiment, female harbor seals fed fish from the polluted Wadden Sea displayed a lower reproductive success than seals fed less contaminated fish from the Atlantic Ocean [96]. In a second long-term feeding study, it was shown that ambient levels of environmental contaminants, notably PCBs, are immunotoxic to harbor seals [100]. In the same study, implantation failure was found to be associated with lower levels of E2 [99].…”
Section: Mammalsmentioning
confidence: 99%
“…De Swart et al (1994Swart et al ( , 1996 performed a feeding study under semifield conditions with harbour seals consuming herring from areas of different contamination levels. Two groups of eleven harbour seals each were housed in two similar basins over a two and a half year period, so that the same individuals could be repeatedly sampled for monitoring of haematological and immunological parameters in regularly taken blood samples.…”
Section: Immunotoxicology Of Persistent Pollutants In Marine Mammalsmentioning
confidence: 99%